1997
DOI: 10.1002/(sici)1097-0258(19971015)16:19<2157::aid-sim653>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dependent errors in the assessment of diagnostic test performance

Abstract: Latent class models can be used to assess diagnostic test performance when there is no perfectly accurate gold standard test available for comparison. These models usually assume independent errors between the tests, conditional on the true disease state of the subject. Maximum likelihood estimates of the prevalence of the disease and the error rates of diagnostic tests are then obtained. This paper examines the impact of error dependencies between binary diagnostic tests on the parameter estimates obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
99
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 4 publications
1
99
0
1
Order By: Relevance
“…There are, however, some important concerns with latent class modelling. There are, for example, important concerns linked to the identifiability of the latent class model (Rindskopf and Rindskopf, 1986;Uebersax and Grove, 1990) and especially the dependence model used (Torrance-Rynard and Walter, 1997;Albert and Dodd, 2004;Albert et al, 2001 Pepe andJanes, 2007). Indeed it must be explicitly recognised that the latent class modelling approach is not a panacea for ground reference data problems.…”
mentioning
confidence: 77%
“…There are, however, some important concerns with latent class modelling. There are, for example, important concerns linked to the identifiability of the latent class model (Rindskopf and Rindskopf, 1986;Uebersax and Grove, 1990) and especially the dependence model used (Torrance-Rynard and Walter, 1997;Albert and Dodd, 2004;Albert et al, 2001 Pepe andJanes, 2007). Indeed it must be explicitly recognised that the latent class modelling approach is not a panacea for ground reference data problems.…”
mentioning
confidence: 77%
“…We also studied the impact of adjusting this model for conditional dependence, i.e., a correlation between BinaxNOW-SP and the reference test within the groups of S. pneumoniae-positive and -negative individuals in each study. We considered models with different degrees of correlation (18) and compared them by using the deviance information criterion (19).…”
Section: Methodsmentioning
confidence: 99%
“…Such a dependence could occur, for instance, between tests which are based on the same underlying principle or between results from the same test at two different points in time. Several authors have demonstrated that it is important to account for this dependence while analyzing the results from diagnostic tests, in order to obtain unbiased estimates of the prevalence of disease and test parameters (Fryback, 1978;Vacek, 1985;Brenner, 1996; Torrance-Rynard and Walter, 1997). While there has been much recent work in this area, the problem of how to analyze diagnostic test data when the tests are correlated and when there is no perfect (gold standard) test remains to be solved, especially when the number of tests available is less than 5, as is usually the case in practice.…”
mentioning
confidence: 99%